EFEKTIVITAS PELAKSANAAN PERSIDANGAN VIRTUAL (ONLINE) PADA PEMERIKSAAN PERKARA PIDANA DI WILAYAH HUKUM PENGADILAN NEGERI PONTIANAK - Anshari Anshari (Jurnal Restorative, 2023)
n social life in recent years (2019-2021), due to the Covid-19 outbreak, a new term has emerged called New Normal, namely the application of social distancing or physical distancing health protocols. The implementation of these health protocols in Indonesia in the past year has had an impact on people's work routines and social interactions. The risk of community infection with the spread of Covid-19 has formed a new habit for many people, such as wearing masks in their daily lives, sitting or standing while keeping their distance, limiting interactions or prohibiting crowds or crowds, to the maximum use of information technology as a means of communication or interaction. Furthermore, drastic changes occur in a short span of time, the reality of life changes unfolds with many challenges. One of them is included in the world of justice in Indonesia. In the Criminal Justice System in Indonesia, so far, of course, it has taken advantage of conventional media, such as the courtroom and its devices, limited communication tools, and other means of examination in court proceedings. Since its launch in 2018 the application of electronic case administration (e-Court) has drastically changed the paradigm which initially required the parties to come directly to the court to register their cases. E-Court is regulated in the Republic of Indonesia Supreme Court Regulation (Perma) Number 1 of 2019 concerning Electronic Administration of Cases and Trials in Courts. Whereas in criminal cases, Virtual (Online) Trials are regulated in Perma RI Number 4 of 2020 concerning Administration and Trial of Criminal Cases in Courts Electronically. However, e-Court itself has not been regulated in the Criminal Procedure Code (KUHAP) as a general provision of criminal procedural law in Indonesia, what should be avoided is that there is a legal vacuum in the formal criminal law. Because this is closely related to the effectiveness of examinations in court hearings, proof by presenting witnesses, experts, evidence. Therefore it is important to conduct research on "The Effectiveness of Implementation of Virtual Trials (Online) in Examining Criminal Cases in the Legal Area of the Pontianak District Court".Keywords: Virtual Trial, Online, Criminal Case, Pontianak District Court